IPTEKS EDUKASI DALAM PENGAMATAN MELAKUKAN TRANSAKSI PERDAGANGAN KOMODITI BERJANGKA PADA PERUSAHAAN PIALANG PT. VICTORY INTERNATIONAL FUTURES - Watupongoh, Sharon Cornelia; Latjandu, Lady Diana (Universitas Sam Ratulangi, 2018)
PT. Victory International Futures was established in 2003 as a brokerage company in the world financial market that uses information technology to support its business. Centered in the city of Surabaya in the heart of the Indonesian business city. PT. Victory International Futures is one of the institutions recognized by the Indonesian government. We provide 100% focus on trading via the internet using the